Analisis Holistik Program KKN Berbasis Asset-Based Community Development (ABCD) di Dusun Kuden: Optimalisasi Sektor Pendidikan, Kesehatan, dan Ekonomi Produktif - Silvi Ana; Alfat Alfat; Muhamad Rinaldi Zahronnizar; Sam Sulaiman; Vinsensiana Nersi; Genoveva Harrtanti; Aco Ma’ruf; Siti Khadijah Kawali; Sahrul Sahrul; Joshua Aristoteles Tafre; Wisnumurti Wisnumurti (Universitas Cokroaminoto Yogyakarta, 2026)
This study examines the design and implementation of a Community Service Program (KKN) based on the Asset-Based Community Development (ABCD) approach, which was carried out holistically and participatively in Kuden Hamlet, Sitimulyo Village, Piyungan Subdistrict, Bantul Regency. This program aims to improve the quality of education, health awareness, and economic independence of the community through integrated interventions. The method used is a qualitative descriptive approach. Data analysis was carried out through data reduction, data display, and drawing conclusions based on the Miles and Huberman model. The results showed a significant increase in community participation, which increased by 25% from previous activities. This active involvement included 25 PAUD students, 40 TPA students, 50 toddlers' parents, 75 elderly people, and 100% active management of KWT Srikandi and Kelompok Mina Kuden. The main indicators of success were measured by consistent attendance, a 100% contribution of land and institutional funds from local assets, as well as an economic shift from a previously non-existent productive economy to the independent cultivation of 500 catfish and agricultural production.These findings confirm that the holistic ABCD-based KKN model is effective in optimizing local assets and promoting sustainable community empowerment.